Cavity Adaptation of Water-Based Restoratives Placed as Liners under a Resin Composite - Sheela B. Abraham; Maria D. Gaintantzopoulou; George Eliades (International Journal of Dentistry)
Purpose. To investigate the cavity adaptation of mineral trioxide (ProRoot MTA/MT), tricalcium silicate (Biodentine/BD), and glass ionomer (Equia Fil/EF) cements used as liners and the interfacial integrity between those liners and a composite resin placed as the main restorative material. Materials and Methods. Standardized class I cavities (n: 8 per group) were prepared in upper premolars. Cavities were lined with a 1 mm thick layer of each of the tested materials and restored with Optibond FL adhesive and Herculite Precis composite resin. Cavity adaptation of the restorations was investigated by computerized X-ray microtomography. The regions of interest (ROI) were set at the cavity-liner (CL) interface and the liner-resin (LR) interface. The percentage void volume fraction (%VVF) in the ROI was calculated. The specimens were then sectioned and the interfaces were evaluated by reflection optical microscopy, to measure the % length (%LD) of the interfacial gaps. Selected samples were further evaluated by scanning electron microscopy. Statistical analysis was performed by two-way ANOVA and Student-Newman-Keuls multiple comparison test (a=0.05). Results. MT showed significantly higher %VVF and %LD values in CL interfaces than BD and EF (p<0.05). No significant differences were found among the materials for the same values at the LR interfaces. Conclusions. When used as a composite liner, ProRoot MTA showed inferior cavity adaptation at dentin/liner interface when compared to Biodentine and Equia Fil.